Model Pendidikan Islam Holistik: Menjawab Kebutuhan Pembentukan Karakter di Era Revolusi Industri 4.0 - Rahmawati, Riza; Saputra, Dedi (Mandalika Institute, 2025)
The Fourth Industrial Revolution has had a profound impact on education, particularly in shaping students’ character. Holistic Islamic education emerges as an integrative approach that unites intellectual, spiritual, emotional, and social aspects to address both moral challenges and the demand for 21st-century competencies. This study aims to formulate a holistic Islamic education model relevant to character building for the younger generation in the digital era. This research employs a qualitative method with a literature review design, applying content analysis. Data were collected from scholarly articles, conference proceedings, books, and official documents, and then analyzed through data reduction, thematic categorization, and synthesis of findings. Source triangulation was applied to ensure validity. The findings reveal that holistic Islamic education effectively integrates religious values with 21st-century skills, such as critical thinking, creativity, communication, and collaboration. The model emphasizes four main dimensions: spirituality (faith and morality), intellectual (knowledge and technology mastery), socio-emotional (empathy and responsibility), and digital-ethics (Islamic-based digital literacy). Practices in Islamic schools and pesantren in Indonesia and Malaysia demonstrate the effectiveness of this model in shaping students who are morally grounded, adaptive, and competitive. Thus, this study highlights the urgency of holistic Islamic education in addressing the challenges of the Fourth Industrial Revolution. The proposed model offers an alternative framework for preparing a globally competitive Muslim generation while preserving their religious identity.